In In Vitro Antibacterial Activity of Green Betel Leaf (Piper betle L.) Extract Against the Growth of Shigella dysenteriae: UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SIRIH HIJAU (Piper betle L.) TERHADAP PERTUMBUHAN BAKTERI Shigella dysenteriae SECARA IN VITRO - Febryawan, Cevin (Barigas: Medical and Health Science Journal, 2026)
Conversely, green betel leaf (Piper betle L.) is rich in bioactive compounds, indicating its promise as a natural source of antibacterial agents. A laboratory-based experimental approach was employed using a post-test only control group design. Green betel leaves were extracted via maceration with 96% ethanol as the solvent. Antibacterial activity was evaluated using the disk diffusion technique on Mueller–Hinton Agar (MHA), applying extract concentrations of 40%, 60%, 80%, and 100%. Ciprofloxacin (5 µg) served as the positive control, while sterile distilled water functioned as the negative control. Data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney U test. The extract produced clear inhibition zones against Shigella dysenteriae, with mean diameters of 9.63 mm at 40%, 13.63 mm at 60%, 15.75 mm at 80%, and 21.13 mm at 100% concentration. The positive control (ciprofloxacin) generated a larger inhibition zone measuring 32.50 mm, whereas no inhibition was observed in the negative control. Based on these findings, the minimum inhibitory concentration was identified at 40%. In vitro testing demonstrated that green betel leaf extract (Piper betle L.) possesses antibacterial activity against Shigella dysenteriae. The strongest inhibitory effect was observed at full-strength extract (100%), while the MIC was established at 40%.